Palladium-Catalyzed Reaction of Arylboronic Acids with Aliphatic Nitriles: Synthesis of Alkyl Aryl Ketones and 2-Arylbenzofurans - Wang, Xingyong; Wang, Xiaodong; Liu, Miaochang; Ding, Jinchang; Chen, Jiuxi; Wu, Huayue (Synthesis, 2013)
An efficient palladium-catalyzed addition of arylboronic acids to aliphatic nitriles has been developed, providing a wide range of alkyl aryl ketones in moderate to excellent yields. It is noteworthy that sequential addition and intramolecular annulation reaction of 2-(2-hydroxyphenyl)acetonitriles with arylboronic acids are also conducted smoothly to afford 2-arylbenzofurans in good yields under the standard conditions.
Keywords: palladium; aliphatic nitriles; arylboronic acids; alkyl aryl ketones; 2-arylbenzofurans